Favoriser les dynamiques inclusives par la médiation : recherche-intervention auprès des lycéen·ne·s et étudiant·e·s atteint·e·s d’une maladie chronique grave - Lucas Sivilotti (Éducation et Socialisation)
While very few studies have examined the experience, schooling, well-being and well-becoming of young adults with serious illnessess, a team has conducted a research project on these health and education investigations. There is a creation of a socio-educational system that proposes mediation activites to accompany this vulnerable population. This article primarly examines how a new actor could participate in inclusive dynamics, wich are co-constructed by the existing ressources and means set up in the academic institutions. Some case studies were carried out from the ethnographic point of view. I used longitudinal observations to study the mediation conducted with four young adults for a year. The analysis of the resultst obtained provides a better understanding of the students’ pathway and the professionnal positionning of the staff involved. Furthemore, it allows me to envisage the deployment of these mediation activities. These interventions have to take into account the current organization of university services and engage all of the actors.